2021
DOI: 10.1542/hpeds.2020-001800
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Management and Outcomes of Children With Complicated Pneumonia

Abstract: OBJECTIVES: To assess the characteristics of children hospitalized with complicated pneumonia at US children’s hospitals and compare these characteristics with those of children hospitalized with community-acquired pneumonia (CAP). METHODS: We identified children hospitalized with complicated pneumonia (parapneumonic effusion, empyema, necrotizing pneumonia, or lung abscess) or CAP across 34 hospitals between 2011 and 2019. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…Our analysis demonstrated an association between longer length of stay and risk of readmission, as supported by a similar study of children with complicated pneumonia [ 39 ]. Contrary to our findings, other observational studies of pediatric readmissions in U.S. children’s hospitals found no meaningful association between index hospitalization length of stay and risk of readmission in children’s hospitals [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis demonstrated an association between longer length of stay and risk of readmission, as supported by a similar study of children with complicated pneumonia [ 39 ]. Contrary to our findings, other observational studies of pediatric readmissions in U.S. children’s hospitals found no meaningful association between index hospitalization length of stay and risk of readmission in children’s hospitals [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis demonstrated an association between longer length of stay and risk of readmission, as supported by a similar study of children with complicated pneumonia [39]. Contrary to these findings, other observational studies of pediatric readmissions in U.S. children's hospitals found no meaningful association between index hospitalization length of stay and risk of readmission in children's hospitals [40,41].…”
Section: Discussionsupporting
confidence: 79%
“…Gross et al previously reported that children hospitalized with complicated pneumonia were more likely to receive MRSA antibiotics than patients with CAP 3 . In our study, we observed an association between empiric MRSA coverage and increased rate of transfer to the ICU, need for mechanical ventilation, and higher H‐RISK score.…”
Section: Discussionsupporting
confidence: 59%
“…Up to 40% of children hospitalized with bacterial pneumonia will develop complicated pneumonia, defined as the development of a parapneumonic effusion/empyema 2 . Compared to children with uncomplicated pneumonia, those with a complicated pneumonia commonly require increased procedural interventions, are more frequently exposed to broad‐spectrum antibiotics, and have prolonged hospitalizations 3 . While the prevalence of bacterial pneumonia has overall declined with routine childhood vaccination, the number of children with complicated disease has remained stable, highlighting the need to identify treatment strategies that optimize care for these patients 1,3 …”
Section: Introductionmentioning
confidence: 99%